High-strength steel grades application for silos structures - Pichugin, Sergiy; Makhinko, Natalia (Academic journal Industrial Machine Building Civil Engineering, 2019)
This paper deals with the work studying of high strength steel in the constructions of silo capacities. The most widespread trademarks of steel have been analyzed. Mechanical and chemical features of examples series of high strength steel of European and American manufacturers have been experimentally tested, which were used for the body’s sheet panels making. It has been made checking calculation of storage capacity with the diameter of 11 m from shaped corrugated sheet of different thickness. The material for panels manufacturing is one of the researched examples of steel. It was mentioned reasonable conclusions according to the using of the concerned material for getting economically rational project decisions.